EFFECTIVENESS OF DEVELOPING DIGITAL TEACHING MATERIALS FOR INDONESIAN LANGUAGE FOR FOREIGN SPEAKERS (BIPA) 1 ON GRAMMAR COMPETENCY BASED ON THE ANIMAKER APPLICATION - Hasna Shofiyah; Dadang Mulyana; Any Budiarti; Wawan Hendrawan (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This research was motivated by the scarcity of Indonesian language teaching materials for foreign speakers (BIPA). The large interest of foreigners in learning Indonesian is still hampered by the lack of availability of BIPA teaching materials. This limited teaching material is an important problem that teachers often face in BIPA learning activities. Therefore, the development of BIPA teaching materials is urgently needed. The problems studied in this research are (1) characteristics of BIPA 1 teaching materials currently used in BIPA learning, (2) development of BIPA 1 teaching materials based on the Animaker application as alternative teaching materials in BIPA learning, (3) feasibility of developing BIPA teaching materials 1 based on the Animaker application in BIPA learning, and (4) the effectiveness of developing BIPA 1 teaching materials based on the Animaker application based on BIPA learners' understanding. This research uses a Research and Development (R&D) approach. This research uses three data collection techniques, namely observation, questionnaires, and documentation to obtain data on the needs for developing teaching materials and evaluating teaching material prototypes. The data sources consist of BIPA teachers, BIPA students and expert lecturers. Data analysis in this research uses descriptive qualitative which consists of data presentation and data conclusions. The results of this research are that BIPA students often feel bored and confused by teaching materials that are only presented in the form of textbooks and very short material. Therefore, teaching materials need to be developed in accordance with Widodo and Jasmadi's theory of teaching material characteristics so that they can support independent learning, deeper understanding, contextualization of material, increased motivation, comprehensive language skills, adaptation to technological developments, learning flexibility, and strengthening skills. grammar. The development of teaching materials through Animaker shows the dominance of changes in substantial and visual aspects, which shows a comparison of characteristics between original and developed teaching materials. The teaching materials developed are more interactive and communicative, so that they can reduce boredom, increase understanding of the material, and increase enthusiasm for learning Indonesian for students